How we did the Question Time Forum (QTF). (July 2015) - Nicola, Pantelis; Fleming-Nouri, Alexander; Belessiotis, Katherine; Daley, Flora; Cartledge, Jonathan
Abstract Background: We piloted a new method of feedback to supplement online surveys and student representation. Methods: The face-to-face feedback session enabled all Year 5 students to ask questions directly to a faculty panel, regarding their curriculum. Questions were gathered in advance so the panel could review and prepare appropriate responses. "Ask the audience" questions were also included. Evaluation: The panel and a convenience sample of 25 students (attenders and non-attenders) were interviewed. All interviews were recorded, transcribed and themed using long table technique. QTF was also evaluated on-the-day by using "Ask the Audience" questions. Results: Sixty-three Year 5 students attended (from a cohort of 337), of whom 96% felt it was a useful addition to current methods of feedback and 93% would attend again. Students felt QTF was "brilliant" and a "triumph in transparency" while the faculty hailed the "novel" event and "honest discussion". Conclusion: QTF was well-received by students and faculty. Both encouraged repetition of the event, thought to enhance the transparency of decisions about the running of the course and promote more in-depth dialogue between staff and students.